Serum concentrations of vascular endothelial growth factor in an infant treated with ranibizumab for retinopathy of prematurity - Robert Hoerster; Philipp S. Muether; Claudia Dahlke; Katrin Mehler; André Oberthür; Bernd Kirchhof; Sascha Fauser (2012)
Editor, Vascular endothelial growth factor (VEGF) is considered to be the major growth factor mediating retinal vascularization in retinopathy of prematurity (ROP). Intravitreal anti-VEGF treatment with bevacizumab has been shown to be effective in treating ROP in the BEAT-ROP trial (Mintz-Hittner et al. 2011). However, bevacizumab escapes from the vitreous into the general circulation and reduces systemic VEGF concentrations for weeks to months (Lee et al. 2011; Sato et al. 2012). Thus, there are concerns about systemic complications, particularly in infants with a very low body weight and rapidly developing tissues. Ranibizumab is an alternative anti-VEGF antibody with similar efficacy as bevacizumab but with the advantage that it does not alter systemic VEGF levels in adults (Carneiro et al. 2012). In ROP treatment, ranibizumab has rarely been used. We present a case report of a very premature infant with ROP that received ranibizumab injections in both eyes. We assessed the effect of ranibizumab on the VEGF concentration in the serum. A male infant born at a gestational age of 22+5 weeks and a body weight at birth of 305 g presented with ROP stage 3 in all quadrants in zones 1–2 with plus disease in both eyes. No tractional retinal detachment or vitreous haemorrhage was present. At the time of diagnosis, the infant was in the 33rd gestational week. Because the avascular zone was located at the border of zones 1 and 2, an intravitreal anti-VEGF therapy with 0.2 mg ranibizumab was chosen for both eyes under local anaesthesia. The parents gave written informed consent on the off-label use of the drug. Plasma samples for routine laboratory tests were collected preoperatively, as well as 1 week, 3 weeks and 4 weeks postoperatively. For safety monitoring, serum VEGF levels were determined by multiplex bead analysis (Luminex, Austin, TX, USA). The procedure did not require approval by the local ethics committee. Three days postoperatively, the plus disease had resolved in both eyes. After one week, regular vascularization of the former avascular area had begun and proceeded in the later course. No tractional retinal detachment and no retinal haemorrhage occurred. Systemic VEGF level was 170.9 pg/ml preoperatively. Postinjection of ranibizumab, systemic VEGF levels were 67.3 pg/ml, 0 pg/ml and 205.8 pg/ml at 1 week, 3 weeks and 4 weeks, respectively (Fig. 1). The detection limit of our assay was <2 pg/ml. Serum VEGF levels pre- and post bilateral intravitreal injection of ranibizumab. Serum VEGF levels decrease post bilateral injection of 0.2 mg of ranibizumab reaching a nadir around 2 weeks and return to normal levels 4 weeks after injection. Abbreviations: inj., intravitreal injection; VEGF, vascular endothelial growth factor; wk, week. In this infant, ranibizumab suppressed systemic VEGF levels below detection limit for about 2 weeks reaching a nadir at 2–3 weeks after intravitreal injection. This suppression may be due to an impaired blood–retinal barrier at this age as ranibizumab does not change systemic VEGF levels in adults (Carneiro et al. 2012). A case series of 11 eyes treated with intravitreal bevacizumab for ROP reported a suppression of systemic VEGF levels for at least 7 weeks postinjection (Lee et al. 2011). In contrast, we show that 4 weeks after bilateral injection of ranibizumab, systemic VEGF has returned to normal levels again. Our data suggest that intravitreal ranibizumab also suppresses systemic VEGF, and therefore systemic side effects cannot be excluded. If anti-VEGF treatment is considered, ranibizumab may be the better choice, as systemic VEGF suppression seems to be shorter than with bevacizumab.